Undervaluing Doctoral Education post COVID - DeLaquil, Tessa; Wang, Lizhou (International Higher Education, 2021)
Undervaluing doctoral education by restricting support for PhD students and programs due to COVID-19 resource losses may shift global talent flows in the immediate future, and potentially in the long run.